Protein folding, cellular stress and cancer - Aranda-Anzaldo, Armando; Dent, Myrna A.R.; Segura-Anaya, Edith; Martínez-Gómez, Alejandro (Progress in biophysics and molecular biology, 2024)
Proteins are acknowledged as the phenotypical manifestation of the genotype, because protein-coding genes carry the information for the strings of amino acids that constitute the proteins. It is widely accepted that protein function depends on the corresponding “native” structure or folding achieved within the cell, and that native protein folding corresponds to the lowest free energy minimum for a given protein. However, protein folding within the cell is a non-deterministic dissipative process that from the same input may produce different outcomes, thus conformational heterogeneity of folded proteins is the rule and not the exception. Local changes in the intracellular environment promote variation in protein folding. Hence protein folding requires “supervision” by a host of chaperones and co-chaperones that help their client proteins to achieve the folding that is most stable according to the local environment. Such environmental influence on protein folding is continuously transduced with the help of the cellular stress responses (CSRs) and this may lead to changes in the rules of engagement between proteins, so that the corresponding protein interactome could be modified by the environment leading to an alternative cellular phenotype. This allows for a phenotypic plasticity useful for adapting to sudden and/or transient environmental changes at the cellular level. Starting from this perspective, hereunder we develop the argument that the presence of sustained cellular stress coupled to efficient CSRs may lead to the selection of an aberrant phenotype as the resulting adaptation of the cellular proteome (and the corresponding interactome) to such stressful conditions, and this can be a common epigenetic pathway to cancer.